Komunikasi Sosial Dalam Menjaga Kerukunan Umat Beragama di Kelurahan Cakranegara Selatan Baru - Wanesari, Sayu Ketut; Prayitno, Joko; Widaswara, Rieka Yulita (IAHN Gde Pudja Mataram, 2023)
Community and religious leaders have a role in maintaining religious harmony in the midst of irregularities that occurred in several neighborhoods in Cakranegara Selatan Baru Village. The aim of the study was to find out the Forms of Communication, Communication Processes and the Impact of Communication of Community Leaders and Religious Leaders in maintaining religious harmony in Cakranegara Selatan Baru Village. The theory used in this research is Laswell's communication theory. The research methodology uses descriptive qualitative methods, with data collection techniques of observation, interviews, and documentation. The results of this study consist of three important points, namely as follows: Forms of communication of community and religious leaders in the North and South Abian Tubuh Sub-District of Cakranegara Selatan Baru, namely interpersonal and group communication. Interpersonal communication is carried out to solve problems faced by the community in the form of disputes, drug arrest cases, fights, so that troubled people get solutions to the problems they face. Both group communication is carried out in coaching and directing activities to the community to be able to tolerate and respect each other to create harmony. The communication process of community and religious leaders consists of five important elements based on the assumptions of Lasswell's communication theory, namely the existence of a communicator consisting of the Head of the neighborhood, Head of RT, Stakeholder and Ustaz. Messages that contain guidance and solutions to the community. Media used orally and in writing. The communicant is the community as the recipient of the guided message. Then the feedback or effect is expected to change people's attitudes and behavior. The impact of the communication of community and religious leaders is the creation of harmonious relationships and an attitude of tolerance that is applied in social life so that harmony can be achieved.